Design of compliant mechanisms with piecewise stiffness variation using self-contact. (September 2022) - Hu, Junfeng; Chen, Weilong; Niu, Jingda
Compliant mechanisms with stiffness variation are required in engineering applications. But most studies in the field of compliant mechanisms have only focused on a mechanism with a single stiffness. This paper presents a design method of compliant mechanisms with multi-level stiffness variation using internal self-contact between rigid parts. The contact changes the reconfigurations of compliant mechanisms to vary their stiffness for a specific motion range. We avoid the need for an external control to achieve piecewise stiffness variation. We derived the general design guideline by which the desired multiple stiffness and motion ranges can be acquired through rational design of the structural parameter. To illustrate the effectiveness of the design idea, we fabricated proof-of-concept prototypes for experimental investigations, and the experimental results demonstrated that the designed compliant mechanism has a multiple-motion range corresponding to different stiffness. The design ideas can also be extended to the multi-axis spatial compliant mechanisms. This design idea enriches the theory and application of compliant mechanisms.